Current concepts in the treatment of hereditary ataxias - Braga, Pedro, Neto; Pedroso, José Luiz; Kuo, Sheng-Han; Marcondes, C. França, Junior; Teive, Hélio Afonso Ghizoni; Barsottini, Orlando Graziani Povoas (Arquivos de Neuro-Psiquiatria, 2016)
Hereditary ataxias (HA) represents an extensive group of clinically and genetically heterogeneous neurodegenerative diseases, characterized by progressive ataxia combined with extra-cerebellar and multi-systemic involvements, including peripheral neuropathy, pyramidal signs, movement disorders, seizures, and cognitive dysfunction. There is no effective treatment for HA, and management remains supportive and symptomatic. In this review, we will focus on the symptomatic treatment of the main autosomal recessive ataxias, autosomal dominant ataxias, X-linked cerebellar ataxias and mitochondrial ataxias. We describe management for different clinical symptoms, mechanism-based approaches, rehabilitation therapy, disease modifying therapy, future clinical trials and perspectives, genetic counseling and preimplantation genetic diagnosis.
Keywords: hereditary ataxias; treatment; rehabilitation therapy; disease modifying therapy